Construction of a preoperative emotional state and postoperative intra-abdominal pressure based prediction model for early enteral feeding intolerance in postoperative patients with gastric cancer - Yingying Xu; Qiongyuan Hu; Dandan Pei; Yin Zhang; Huanhuan Zhu; Yan Hui; Wenxian Guan; Meiling Xu; Li Chen (Frontiers in Nutrition)
BackgroundThe incidence of enteral feeding intolerance (ENFI) in the early postoperative period is high in patients after gastric cancer resection due to the characteristics of surgical traumatic stress and changes in the physiological structure of the digestive tract, and the current evaluation of ENFI after gastric cancer resection mostly depends on the symptoms and complaints of patients after gastric cancer resection, which is lagging and subjective. Early accurate and objective prediction of the risk of early ENFI after gastric cancer resection is critical to guide clinical enteral nutrition practice.Materials and methodsThis study included 470 patients who underwent radical gastric cancer surgery at the Division of Gastric Surgery of a tertiary hospital in Nanjing, Jiangsu Province, between November 2021 and October 2022. The patients were divided into a training set (n = 329) and a validation set (n = 141) in a 7:3 ratio. The predictors were first screened through Lasso regression. Subsequently, multifactorial logistic regression analysis was used to establish a model for predicting patients' early ENFI column charts after gastric cancer resection. Internal and external validation of the model were performed on the training set and validation set data, respectively, including plotting the area under the curve (AUC) of the receiver operating characteristic (ROC) curve and calibration curves to assess the differentiation and calibration of the prediction model. The Hosmer-Lemeshow test was also used to assess the fit of the model.ResultsThe incidence of early ENFI in postoperative patients with gastric cancer was 44.68% in the training set and 43.97% in the validation set. The final predictors entered into the model were enteral nutrition solution type (OR1 = 1.31/OR2 = 7.23), preoperative enteral nutrition pre-adaptation technique (OR = 0.29), surgical approach (OR = 2.21), preoperative Profile of Mood State-Short Form score (OR = 5.07), and intra-abdominal pressure (OR = 6.79). In the internal validation, the AUC was 0.836, the 95% CI ranged from 0.792 to 0.879, the Hosmer-Lemeshow test showed χ 2 = 4.368 and P = 0.737, the sensitivity was 0.775, and the specificity was 0.741. In the external validation, the AUC was 0.853, the 95% CI ranged from 0.788 to 0.919, the Hosmer-Lemeshow test showed χ2 = 13.740 and P = 0.089, the sensitivity was 0.785, and the specificity was 0.823.ConclusionsThe Nomogram model of early ENFI in postoperative patients with gastric cancer, constructed on the basis of Lasso-logistic regression, had good predictive efficacy and may serve as a reference for healthcare professionals to identify high-risk patients with early ENFI after gastrectomy.